DYNAMICS OF THE BILCHENOK SURGING GLACIER IN THE KLYUCHEVSKAYA VOLCANO GROUP - Ya. D. Muraviev; D. G. Tsvetkov; A. Ya. Muraviev; G. B. Osipova (Лëд и снег, 2015)
SummaryEvolution of the Bilchenok surging glacier in Kluchevskaya group of volcanoes,Kamchatka, from the end of XIX century to now is presented. After retreat in the beginning of XX century, the glacier became more active and advanced in the late forties. The powerful surge of the glacier has occurred in 1959/60 when its terminus has promoted on2 kmand has gone down to height of 615–630 m in birch forest. During the next glacier advance (1982–1984), glaciological and volcanological researches were done on its tongue. Scale of this advance were less considerable, than the surge of 1959, and the volume of transferred ice was as great as about 35–40 million t., that is 3.5 times less than at the previous one. During the advance of Bilchenok Glacier in 1980–1983, seismic activity near Ushkovsky volcano was marked. We can assume that advance and character of its development are appreciably connected with strengthening of seismic activity, and with the raised thermal stream in caldera of the Ushkovsky volcano, influencing temperature and rheological properties of ice. The large surge of Bilchenok Glacier in 1959–1960 was preceded by a smaller advance, which has led to increase in constraining «stopper» in a trailer part of the glacier and to additional pressure on an overlying site up to a sole of icefall. Nowadays the glacier advances again.